2022
DOI: 10.1159/000525309
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Response and SARS-CoV-2 Infection Risk following the Third and Fourth Doses of the BNT162b2 Vaccine in Dialysis Patients

Abstract: The optimal SARS-CoV-2 vaccination schedule in dialysis patients and the potential need for a fourth vaccine dose are debatable. We prospectively assessed the humoral responses to three and four doses of BNT162b2 among dialysis patients. The study included 106 dialysis patients; 60 (56.6%) and 46 (43.4%) received 3 and 4 vaccine doses, respectively. Anti-spike (anti-S) antibody titers significantly increased after the third vaccine dose, followed by a decline, yet still remained higher than all previous measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 9 publications
3
21
0
Order By: Relevance
“…The progressive decrease in antibody titers over time after each vaccination dose is a cause for concern. Previous reports have shown that 3 to 6 months after initial vaccination and booster doses, significant anti-spike titer decline is observed in dialysis patients [ 12 , 24 ]. At present, individualizing additional dose prescriptions is probably the best strategy to obtain an optimal immune response, avoiding the risk of hyperstimulation and immune exhaustion [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The progressive decrease in antibody titers over time after each vaccination dose is a cause for concern. Previous reports have shown that 3 to 6 months after initial vaccination and booster doses, significant anti-spike titer decline is observed in dialysis patients [ 12 , 24 ]. At present, individualizing additional dose prescriptions is probably the best strategy to obtain an optimal immune response, avoiding the risk of hyperstimulation and immune exhaustion [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…7,8,15,24 However, longer-term studies following the immune response after third doses have so far been limited by sample size and infrequent assessment. 11,12 This study used six months of post-third dose data to show that third doses also improved durability of the immune response. Specifically, among those without history of COVID-19, median [IQR] titer was 150 [42, 471] BAU/mL at six months in the initial series cohort, similar to our prior findings, 4,13 but 1288 [512, ≥ 1781] BAU/mL at six months in the third dose cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The initial augmentation of the immune response by additional vaccine doses is well-established, 7,8 but longer term studies have been limited by small sample size and infrequent monitoring. 11,12 In this study, we used serially collected antibody data to 1) identify previously unrecognized SARS-CoV-2 infections based on an increase in titer, and 2) characterize the trend of antibody titer levels over six months after additional vaccine doses.…”
Section: Introductionmentioning
confidence: 99%
“…The fourth vaccine dose led to another profound rise in anti-S titres, and the absolute increase following the fourth dose correlated with the response to the third dose in dialysis patients Einbinder et al 49 No adverse events were reported Abbreviation: SARS-CoV-2, severe acute respiratory syndrome coronavirus 2.…”
Section: Bnt162b2mentioning
confidence: 97%